The Effect of Asymptomatic and/or Treated Brain Metastases on Efficacy of Immune Checkpoint Inhibitors in Metastatic Non–Small Cell Lung Cancer: A Meta-Analysis - Li, Sihan; Zhang, Hongwei; Liu, Tingting; Chen, Jun; Dang, Jun (Frontiers in Oncology, 2021)
Background To assess the effect of asymptomatic and/or treated brain metastases (BMs) on the efficacy of immune checkpoint inhibitors (ICIs) in metastatic non-small cell lung cancer (NSCLC). Patients and Methods PubMed, Embase, Cochrane Library, Web of Science, and recent meetings were searched for randomized controlled trials (RCTs). The primary outcomes of interest were overall survival (OS) and progression-free survival (PFS). Results Seventeen articles reporting 15 RCTs with 10,358 patients (1,199 with and 9,159 without BMs) were eligible. ICIs were associated with longer OS and PFS than those in chemotherapy either in patients with (hazard ratio [HR], 0.65; 95% confidence interval [CI], 0.51–0.82 and HR, 0.60; 95% CI, 0.45–0.79) or without BMs (HR, 0.74; 95% CI, 0.70–0.78 and HR, 0.70; 95% CI, 0.57–0.86); no significant difference in the pooled HRs for OS (Pinteraction = 0.29) and PFS (Pinteraction = 0.37) was observed between the two patient populations. Subgroup analyses revealed that either ICI monotherapy or combination therapy significantly improved OS and PFS compared with those in chemotherapy both for patients with and without BMs. Superior OS benefit from ICI combination therapy than that in monotherapy was observed in patients with BMs (HR, 0.49 vs. 0.81, Pinteraction = 0.005) but not in patients without BMs (HR, 0.71 vs. 0.76, Pinteraction = 0.27). Conclusion There was no compelling statistical evidence that the efficacy of ICIs in metastatic NSCLC was modified by the presence of asymptomatic and/or treated BMs. Patients with BMs were likely to obtain more OS benefit from ICI combination therapy than that from monotherapy.